2002
DOI: 10.1590/s0036-46652002000100002
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of serum anti-cysticercus antibodies in the population of a rural Brazilian community (Cássia dos Coqueiros, SP) determined by ELISA and immunoblotting using Taenia crassiceps antigens

Abstract: Considering the impact of cysticercosis on public health, especially the neurologic form of the disease, neurocysticercosis (NC), we studied the frequency of positivity of anti-Taenia solium cysticercus antibodies in serum samples from 1,863 inhabitants of Cássia dos Coqueiros, SP, a municipal district located 80 km from Ribeirão Preto, an area considered endemic for cysticercosis. The 1,863 samples were tested by enzyme linked immunosorbent assay (ELISA) using an antigenic extract from Taenia crassiceps vesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
1
4

Year Published

2003
2003
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 24 publications
1
17
1
4
Order By: Relevance
“…ELISA tests showed sensibility of 100% in patients diagnosed with NC in our survey. The frequency of anti-T. solium cysticercus antibodies in the studied population is higher than those found by Bragazza et al (2002), using a similar methodology in a population of Cássia dos Coqueiros (2.1%), a rural area near Ribeirão Preto, São Paulo, also considered an endemic region for cysticercosis. Surveys by ELISA by Vaz et al (1990) in a population from five counties of São Paulo, and Silveira-Lacerda et al (2002) in blood donors from four cities in Minas Gerais found a frequency of anti-T. solium cysticercus antibodies of 2.3 and 5.6% respectively.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…ELISA tests showed sensibility of 100% in patients diagnosed with NC in our survey. The frequency of anti-T. solium cysticercus antibodies in the studied population is higher than those found by Bragazza et al (2002), using a similar methodology in a population of Cássia dos Coqueiros (2.1%), a rural area near Ribeirão Preto, São Paulo, also considered an endemic region for cysticercosis. Surveys by ELISA by Vaz et al (1990) in a population from five counties of São Paulo, and Silveira-Lacerda et al (2002) in blood donors from four cities in Minas Gerais found a frequency of anti-T. solium cysticercus antibodies of 2.3 and 5.6% respectively.…”
Section: Resultscontrasting
confidence: 54%
“…In the state of São Paulo, the frequency of anti-T. solium cysticercus antibodies in humans was determined in few counties (Vaz et al 1990, Bragazza et al 2002. Nonetheless, studies about the prevalence of T. saginata infection in humans or the presence of T. saginata cysticercus in cattle are scarce (Ungar & Germano 1992).…”
mentioning
confidence: 99%
“…The population studied range in age from six to 81 years with the adults' serum samples being more reactive. The results agreed with other studies 1,3,5 , indicating that the higher prevalence among adults was presumably due to their longer period of exposure and/or different immune response 15 .…”
supporting
confidence: 91%
“…In the non NC group we obtained positive results mainly with the Tso antigen. The specificity of the ELISA with Tcra-vf has been reported as 80% and 96% by BUENO et al 5 and BRAGAZZA et al 4 , respectively, while PERALTA et al 17 reported 98% specificity for ELISA with 14 kDa glycoprotein of T. crassiceps. In this study the Tcra-gp antigen showed similar sensitivity and better specificity than that of Tcra-vf, so Tcra-gp seems to be the best choice to be attempt in order to improve the specificity of ELISA for screening purpose and efforts are underway through purification of the specific and immunodominant antigens.…”
Section: Discussionmentioning
confidence: 97%